2008
DOI: 10.1021/jp712029w
|View full text |Cite
|
Sign up to set email alerts
|

Nonoxidative Coupling of Methane over Supported Ceria Photocatalysts

Abstract: Various silica-supported rare earth oxides were examined for photocatalytic methane conversion around room temperature. Among them, silica-supported cerium oxide with low loading amount showed the highest photoactivity for nonoxidative coupling of methane (NOCM) to produce both ethane and hydrogen. XANES, DR UV−vis, and phosphorescence spectra of silica-supported cerium oxide revealed that the main species on the low loading samples were highly dispersed Ce(III) oxides, suggesting that they were the photocatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 57 publications
0
36
0
2
Order By: Relevance
“…However, among the silica-supported rare earth oxides prepared by impregnation method, only silica-supported cerium oxide showed a significant activity for the NOCM. 20 The highly dispersed Ce(III) oxide species that were excited by 265 nm UV light were revealed as the active sites for the NOCM. These active species were mainly obtained when the loading amount of Ce was low, such as 0.1 mol% or less.…”
Section: Rsi-ohmentioning
confidence: 99%
“…However, among the silica-supported rare earth oxides prepared by impregnation method, only silica-supported cerium oxide showed a significant activity for the NOCM. 20 The highly dispersed Ce(III) oxide species that were excited by 265 nm UV light were revealed as the active sites for the NOCM. These active species were mainly obtained when the loading amount of Ce was low, such as 0.1 mol% or less.…”
Section: Rsi-ohmentioning
confidence: 99%
“…It is now a consensus that the H 3 CÀH bond cleavage process is a key step in the dehydrogenation and dimerization of methane. [6,11] Herein, we describe a Ga 3+ -modified ETS-10 zeolite material (ETS-10 = titanosilicate) in which the photogenerated hydroxyl radical and the extraframework metal ion interact with the methane molecule to split the H 3 CÀH bond in a synergistic way under UV irradiation (l < 350 nm). Nevertheless, only limited information about the mechanism for the photoinduced cleavage of the H 3 C À H bond occurring on substrate surfaces has been revealed so far, [9] and the nature of the photoactive species responsible for the methane C À H activation has yet to be elucidated in more detail.…”
mentioning
confidence: 99%
“…One considers that the presence of oxygen-centered radicals brings about homolytic CÀH bond cleavage, [10] whereas in the other highly dispersed metal species are believed to be the active sites of methane dehydrogenation. [6,11] Herein, we describe a Ga 3+ -modified ETS-10 zeolite material (ETS-10 = titanosilicate) in which the photogenerated hydroxyl radical and the extraframework metal ion interact with the methane molecule to split the H 3 CÀH bond in a synergistic way under UV irradiation (l < 350 nm). It is demonstrated that the combination of both oxygen-centered and metal-centered active sites in the material significantly enhances its photoactivity for methane CÀH bond activation, leading to efficient non-oxidative coupling of methane at room temperature.…”
mentioning
confidence: 99%
“…[181] Ferner wurde dargelegt, dass reine Siliciumdioxidmaterialien, die zuvor bei hoher Te mperatur entgast worden sind, bei Raumtemperatur unter Lichtbestrahlung NOCM fçrdern kçnnen. [183][184][185] Hochdispergiertes Titanoxid und Ceroxid auf Siliciumdioxid zeigten ebenfalls eine hohe AktivitätfürNOCM. B.…”
Section: Lichtgetriebene Nichtoxidative Kupplung Von Methanunclassified
“…Die katalytische Leistung von Siliciumdioxid konnte durch Einführen bestimmter Metallkationen, wie Al, Mg und Zr, mit geringer Konzentration erhçht werden. [183][184][185] Hochdispergiertes Titanoxid und Ceroxid auf Siliciumdioxid zeigten ebenfalls eine hohe AktivitätfürNOCM. [186] [189,190] Auch die direkte Umwandlung von CH 4 in nützliche Verbindungen fürd ie Synthese,w ie Olefine und Arene,g ewinnt zunehmend an Aufmerksamkeit.…”
Section: Lichtgetriebene Nichtoxidative Kupplung Von Methanunclassified